2015
DOI: 10.1071/mf13322
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of sharptooth catfish, Clarias gariepinus (Burchell, 1822) (Clariidae), in the Lower Okavango Delta, Botswana

Abstract: Managing any inland fishery requires reliable age data and accurate estimates of growth rate. Clarias gariepinus, the largest catfish species in most tropical African floodplain river systems, is an important constituent of subsistence fishery catches. We used otolith-derived age estimates to describe patterns of age and growth for C. gariepinus from the Lower Okavango Delta in northern Botswana. Edge analysis of sectioned sagittal otoliths showed that growth zone deposition occurred during the annual flood pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Dudley [56] also observed that growth of floodplain fish differed significantly among years driven by flooding and temperature. While some studies have observed no size differences for Clarias gariepinus in the Delta, upper Delta populations follow K life histories while lower Delta populations are more r selected [77], [80]. The feeding ecology of most floodplain fish species is flood-pulse driven [46].…”
Section: Adult Fishmentioning
confidence: 97%
See 3 more Smart Citations
“…Dudley [56] also observed that growth of floodplain fish differed significantly among years driven by flooding and temperature. While some studies have observed no size differences for Clarias gariepinus in the Delta, upper Delta populations follow K life histories while lower Delta populations are more r selected [77], [80]. The feeding ecology of most floodplain fish species is flood-pulse driven [46].…”
Section: Adult Fishmentioning
confidence: 97%
“…Serranochromis macrocephalus and C. rendalli) was significantly associated with water temperature , which agrees with van der Waals [72]observations. Growth and Feeding: Floodplain fish growth is fastest during increasing water levels [78]- [80] and peaks at maximum flooded area to take advantage of the available food in the floodplains [57], [80]. During the low flood season intra-specific competition for food [46] decreases fish growth rates [56], [81].…”
Section: Adult Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also an indication of a healthy stock that is under exploited thus agreeing with Mosepele (unpublished) who found that Maximum Sustainable Yield could not be reached for C. gariepinus in the Okavango Delta. Future studies should aim to conduct fi shery dependent selectivity studies in the Lower Okavango Delta to see if selectivity changes with location, gear or target species (Baremore et al 2012), particularly because recently, studies have suggested the possibility of two distinct populations of C. gariepinus between the Upper and Lower Okavango Delta (Bokhutlo et al 2015).…”
Section: Conclusion and Management Recom-mendationsmentioning
confidence: 99%